Enzyme replacement therapy with agalsidase alfa in patients with Fabry's disease: an analysis of registry data - Mehta, Atul B.; Ries, Markus (The lancet, 2009)
Summary - Background - We analysed 5-year treatment with agalsidase alfa enzyme replacement therapy in patients with Fabry's disease who were enrolled in the Fabry Outcome Survey observational database (FOS). - Methods - Baseline and 5-year data were available for up to 181 adults (126 men) in FOS. Serial data for cardiac mass and function, renal function, pain, and quality of life were assessed. Safety and sensitivity analyses were done in patients with baseline and at least one relevant follow-up measurement during the 5 years (n=555 and n=475, respectively). - Findings - In patients with baseline cardiac hypertrophy, treatment resulted in a sustained reduction in left ventricular mass (LVM) index after 5 years (from 71·4 [SD 22·5] g/m2·7 to 64·1 [18·7] g/m2·7, p=0·0111) and a significant increase in midwall fractional shortening (MFS) from 14·3% (2·3) to 16·0% (3·8) after 3 years (p=0·02). In patients without baseline hypertrophy, LVM index and MFS remained stable. Mean yearly fall in estimated glomerular filtration rate versus baseline after 5 years of enzyme replacement therapy was −3·17 mL/min per 1·73 m2 for men and −0·89 mL/min per 1·73 m2 for women. Average pain, measured by Brief Pain Inventory score, improved significantly, from 3·7 (2·3) at baseline to 2·5 (2·4) after 5 years (p=0·0023). Quality of life, measured by deviation scores from normal EuroQol values, improved significantly, from −0·24 (0·3) at baseline to −0·17 (0·3) after 5 years (p=0·0483). Findings were confirmed by sensitivity analysis. No unexpected safety concerns were identified. - Interpretation - By comparison with historical natural history data for patients with Fabry's disease who were not treated with enzyme replacement therapy, long-term treatment with agalsidase alfa leads to substantial and sustained clinical benefits. - Funding - Shire Human Genetic Therapies AB.
Gesehen am 08.05.2019